Tercera edad empoderada y cultura urbana expulsiva en Latino America - Klein, Alejandro (SocietàMutamentoPolitica, 2018)
In this paper are presented one reflection about how some authors study the social tissue and the urban culture, and how this last one is articulated with the themes of inclusion or exclusion in the latin american ageing. It also takes into account social situations that allow further assume the existence of integration processes with other expulsive. Both of them, with a high level of complexity and heterogeneity, especially since the Latin-American reality. One group especially vulnerable to policies of expulsion is of aging, who are in a swing between a situation of vulnerable not-citizenship and a renewal of their agenda of citizen and participatory rights.